2010
DOI: 10.1089/vbz.2009.0109
|View full text |Cite
|
Sign up to set email alerts
|

Re-Emergence of Dog Rabies in Mpumalanga Province, South Africa

Abstract: Dog rabies has commonly been associated with the eastern and southern border areas in Mpumalanga province, and the Nkomazi district in the east has been most affected. In other parts of the province, canid rabies has been under control for many years; however, in 2008, dog rabies spread to other parts of the province and resulted in a widespread outbreak. The objective of this study was to genetically characterize rabies viruses in an attempt to determine the source of this recent outbreak. Fifty-five rabies v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 17 publications
(27 citation statements)
references
References 10 publications
1
26
0
Order By: Relevance
“…There are no private veterinary services in the study area. The provincial state veterinary services have strengthened regular dog rabies vaccination campaigns since the disease re-emerged in Bushbuckridge in 2008, after a long period of apparent absence [ 22 ]. In addition to the veterinary services provided by the state, the animal health needs of the community in Hluvukani and the surrounding areas are also met at a subsidised rate by the Hluvukani Animal Clinic, located in the centre of Hluvukani and run by the Faculty of Veterinary Science of the University of Pretoria (UP).…”
Section: Methodsmentioning
confidence: 99%
“…There are no private veterinary services in the study area. The provincial state veterinary services have strengthened regular dog rabies vaccination campaigns since the disease re-emerged in Bushbuckridge in 2008, after a long period of apparent absence [ 22 ]. In addition to the veterinary services provided by the state, the animal health needs of the community in Hluvukani and the surrounding areas are also met at a subsidised rate by the Hluvukani Animal Clinic, located in the centre of Hluvukani and run by the Faculty of Veterinary Science of the University of Pretoria (UP).…”
Section: Methodsmentioning
confidence: 99%
“…To date, the only molecular epidemiological study to include isolates from Mozambique was an investigation focused on the genetic relatedness of RABV isolates in the Mpumalanga province of South Africa. In that study, nucleotide sequences of two RABV isolates from Mozambique were compared to RABV sequences from Mpumalanga province and were delineated into a distinct cluster (Mkhize et al 2010 ).…”
Section: Introductionmentioning
confidence: 99%
“…In another study, dog brain tissue samples were collected from the Mpumalanga and KwaZulu-Natal provinces and investigated for rabies infection using RNA extraction followed by reverse-transcription PCR and sequencing. The phylogenetic analysis confirmed that the virus sequences obtained from the Mpumalanga and KwaZulu-Natal provinces shared a common origin [273]. Interestingly, rabies from dogs has been transmitted to wild canids, including the species of jackal and foxes [274].…”
Section: South Africamentioning
confidence: 70%